Strategic Innovation Quality: Technological Innovation Capability Model to Improve Competitive Advantage and Human Resource Performance of Tourism Industry - Sudiyono, Sudiyono; Nurcahyo, Satria Avianda; Widagdo, Teguh Harso (Universitas Dian Nuswantoro Semarang, 2025)
This study aims to analyze the influence of Strategic Innovation Quality (SIQ) on Competitive Advantage (CA) and Human Resource Performance (HRP), with Technological Innovation Capability (TIC) as a mediating variable. The research was conducted on employees of Lawu Group Tourist Attractions in Central Java, with a saturated sample of 255 employees. A quantitative research method was applied using Structural Equation Modeling-Partial Least Squares (SEM-PLS).The results indicate that SIQ has a positive influence on TIC and HRP. TIC also has a positive and significant impact on CA and HRP, while it mediates the relationship between SIQ and CA. However, the direct relationship between SIQ and CA is not significant, suggesting that technological innovation capability plays a more dominant role in creating a competitive advantage than strategic innovation alone. These findings highlight that in the tourism industry, strengthening technological innovation capabilities is crucial for enhancing both competitive advantage and human resource performance.The study's implications suggest that the management of Lawu Group Tourist Attractions should focus on strengthening technological innovation strategies to enhance competitiveness and optimize employee performance. Moreover, organizations need to emphasize technology development as a bridge between strategic innovation and competitive advantage. This research contributes academically to the development of strategic innovation theories in the tourism sector and provides practical recommendations for tourism destination managers to improve organizational performance sustainably.